2021
DOI: 10.32553/ijmbs.v5i12.2328
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Profile of Dengue Patients in Children

Abstract: Background: To study the clinical profile of dengue in children Methods: The hospital based study was conducted on patients presenting to paediatric hospital, who fulfilled inclusion and exclusion criteria. Results: Based on the symptoms, the most common symptoms noticed were fever 94.00% followed by myalgia 85.00% decreased appetite 83%, retroorbital pain in 84.0%  and vomiting 81.00% Conclusion: It concluded that  common symptoms observed were fever, myalgia, decreased appetite and headache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Tribal festivals, ceremonial practices, religious systems, and traditions play a significant role in tribal culture and have a distinctive place in Indian society Meena & Meena (2014). It showcases their rich heritage.…”
Section: Festivalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tribal festivals, ceremonial practices, religious systems, and traditions play a significant role in tribal culture and have a distinctive place in Indian society Meena & Meena (2014). It showcases their rich heritage.…”
Section: Festivalsmentioning
confidence: 99%
“…Gonds were originally not Hindus however, the Hindus have had a significant impact on the Gonds' religious beliefs. They have long practiced Hindu culture and traditions Meena & Meena (2014). However, it's interesting to note that the Gonds believe they entered the domain of the gods later because of Karta Subal, the son of Shiva Mehta (1984):177.…”
Section: Religionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, when beneficial organisms are required for the main crop, mowing the cover crop facilitates the early migration of beneficial organisms to the main crop. 47 Further, the use of brassicas (rapeseed and mustard, radish, cabbage, canola) is another unique strategy, wherein the brassicas are grown as cover crops which are subsequently buried in the surface soil using a hand plough or soil turning plough, and on the decomposition, various substances released reduces nematode population drastically. 23 Furthermore, Nicholls et al (2001), 49 showed that mowing of alternate cover crop rows pushes Anagrus wasps and various other predators onto the main crop vines.…”
Section: Cover Cropsmentioning
confidence: 99%